Saxagliptin enhances osteogenic differentiation in MC3T3-E1 cells, dependent on the activation of AMP-activated protein kinase α (AMPKα)/runt-related transcription factor-2 (Runx-2). Issue 1 (1st January 2022) - Wang, Qiang; Xie, Xiaoxing; Zhang, Dehua; Mao, Feng; Wang, Shaobo; Liao, Yi
ABSTRACT: Osteoporosis is a metabolic bone disease commonly observed in the elderly, and its pathogenesis is associated with declined osteogenic differentiation. Osteogenic differentiation could be facilitated by the activation of the AMP-activated protein kinase (AMPK) pathway. Saxagliptin, an anti-diabetic agent with inhibitory effects against dipeptidyl peptidase 4 (DPP-4), has been recently reported to induce the activation of the AMPK pathway. The present study proposes to explore the function and mechanism of Saxagliptin in osteogenic differentiation. Osteogenic differentiation induction medium (ODIM) was utilized to induce osteogenic differentiation in MC3T3-E1 cells. Significantly increased mineral nodule formation, elevated alkaline phosphatase (ALP) activity, and upregulated expression of osteogenic marker genes activating transcription factor-4 (ATF-4), osteopontin (OPN), and type I collagen (Col1) were observed in ODIM-cultured MC3T3-E1 cells, all of which were further enhanced by the introduction of Saxagliptin. The elevated expression level of runt-related transcription factor-2 (Runx-2), an important transcriptional factor involved in the progression of osteogenic differentiation, in ODIM-cultured MC3T3-E1 cells was further promoted by Saxagliptin. The AMPK pathway in ODIM-cultured MC3T3-E1 cells was significantly activated by Saxagliptin, and the functions of Saxagliptin in promoting osteogenic differentiation were abolished by compound C, the inhibitor of the AMPK pathway. Conclusively, Saxagliptin enhanced osteogenic differentiation in MC3T3-E1 cells, dependent on the activation of AMPKα/RUNX-2.